Multi-layer clustering routing algorithm for wireless vehicular sensor networks - Liu, Y.; Xiong, N.; Zhao, Y.; Vasilakos, A.V.; Gao, J.; Jia, Y. (IET communications, 2010)
Recently, there is a strong interest in developing wireless sensor network (WSN) techniques and important applications for moving vehicles, to enable WSN communication between roadside and vehicles or between vehicles. Wireless vehicular sensor networks (VSNs) using all kinds of routing algorithms of low-energy efficiency has recently received considerable attention. Clustering algorithm has a significant impact on the operation of WSN. An effective clustering algorithm leads WSN to operate efficiently. Hierarchical clustering is a new clustering scheme in WSN. This study presents a novel vehicular clustering scheme integrating hierarchical clustering on the basis of classical routing algorithm. Simulation results show that the new scheme efficiently mitigates the hot spot problem in WSN and achieves much improvement in network lifetime and load balance compared to the old algorithm which is Direct, LEACH and DCHS.